Ensiklopedi syirik & bid'ah Jawa - Suwaidi, Fahmi; Aman, Abu. (Gonilan, Kartasura, Solo : Aqwam Media Profetika, 2011)
Acculturation of Javanese and Islamic culture.
Includes bibliographical references (p. 196).
Keywords: Islam -- Indonesia -- Java -- Customs and practices; Java (Indonesia) -- Civilization -- Islamic influences